Rotor Position PLTGU 1.1 UP Muara Tawar - Sahlan Sahlan; Erlina Erlina; Pranoto Yulistyo (Sekolah Tinggi Teknik - PLN, 2016)
Maintenance of generating units is done regularly based on specific operating hours and in various types of maintenance, inspections and overhauls. Each overhoul performed and maintenance unit is not operating in the maintenance period. Thus the implementation of maintenance should be done as effectively and efficiently as possible. Rotor position one of the activities in overhoul that much help and determine the smoothness pealaksanaan overhoul. With peaksanaannya smooth and maximum results will help peaksanaan other activities so that implementation can overhoul more effective and targeted.